The Cyclonic Eddy Train in the Indian Ocean Sector of the Southern Ocean as Revealed by Satellite Radar Altimeters and In Situ Measurements. Issue 6 (9th June 2020) - Mizobata, K.; Shimada, K.; Aoki, S.; Kitade, Y.
Abstract: We investigated dynamic ocean topography (DOT) to reveal the oceanic subpolar circulation and possible pathway of modified Circumpolar Deep Water (CDW) in the Indian Ocean sector of the Southern Ocean. Satellite radar altimeter data sets were employed to develop monthly DOT in both open water and ice‐covered areas throughout the course of a year. A 0.2° × 0.2° gridded DOT was reconstructed for investigation of the oceanic structure at fine scale. The reconstructed DOT exhibited a "cyclonic eddy train" consisting of the Vincennes eddy, Poinsett eddy, and Sabrina eddies. The relationship between the depth of each eddy and the wind curl showed negative correlations for the Vincennes eddy and Sabrina eddies during wintertime only. Therefore, winds are not the main drivers of the eddies. A hydrographic section in 2017 clearly revealed the vertical structure of the Vincennes eddy. The absolute velocity estimated by the DOT and in situ geostrophic velocity showed equatorward Antarctic Bottom Water (AABW) transport at 6–8 cm s −1 on the western side and poleward transport of CDW at 3–4 cm s −1 on the eastern side of the Vincennes eddy. The net transports of the AABW and CDW layers in the Vincennes eddy were 0.6 ± 0.4 Sv (equatorward) and 0.5 ± 0.36 Sv (poleward), respectively. The order of magnitude of the AABW current speed was confirmed by in situ mooring data. The vertical profiles of absolute velocity suggest the possibility of estimating CDW transport using a satellite altimeter. Plain Language Summary: In the Indian Ocean sector of the Southern Ocean, the basal melt of the Totten Ice Shelf due to warm deep water is notable. Previous ship observations suggest that warm water is accessing the shelf but are unclear as to how the warm water approaches the continental shelf. In this study, we used satellite observations to investigate ocean circulation in this area in detail. We found the presence of a cyclonic eddy train, which may facilitate water transport across the shelf. The temporal variabilities of the cyclonic eddy train cannot be explained by wind forcing alone. Satellite and in situ measurements reveal how deep water approaches the shelf break via the Vincennes eddy, the western most eddy of the train. A combination of measurements indicates that the main structure of Vincennes eddy circulation can be detected at the sea surface, which implies that the transport of warm water can be monitored from space. Key Points: A cyclonic eddy train in the Indian Southern Ocean was revealed by a combination of satellite and in situ measurements Vincennes eddy transports 0.6 ± 0.4 Sv of Antarctic Bottom Water equatorward and 0.5 ± 0.36 Sv of Circumpolar Deep Water poleward The poleward transport of Circumpolar Deep Water due to the cyclonic eddies could be monitored by satellite altimeters